2021
DOI: 10.3390/app11115173
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Atomization and Its Drug Delivery and Biomedical Applications

Abstract: Atomization is an intricate operation involving unstable and complex networks with rupture and fusion of liquid molecules. There are diverse details that typify the spray formation, which are the technique and configuration of the atomization process, dimension and structure of the nozzle, experimental parameters, etc. Ultimately, the process generates fine sprays from the bulk of a liquid. Some examples of atomization that we come across in our day-to-day life are antiperspirant or hair spray, shower head, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…A survey of the literature reveals a wide variation in the size of the aerosols (0.1–100 μ m) produced from commercially available aerosol generators (inhalers, nebulizers etc.) [ 3 ]. Basu et al [ 24 ] reported a mass median diameter larger than 40 μ m, while Kooji et al [ 2 ] reported the mass median diameter of aerosols produced from various ultrasonic nebulizers to be in the range of 1–10 μ m although larger droplets (∼50 μ m) were also observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of the literature reveals a wide variation in the size of the aerosols (0.1–100 μ m) produced from commercially available aerosol generators (inhalers, nebulizers etc.) [ 3 ]. Basu et al [ 24 ] reported a mass median diameter larger than 40 μ m, while Kooji et al [ 2 ] reported the mass median diameter of aerosols produced from various ultrasonic nebulizers to be in the range of 1–10 μ m although larger droplets (∼50 μ m) were also observed.…”
Section: Resultsmentioning
confidence: 99%
“…The drug molecules may be in the form of dry powders or liquid aerosols, and are administered in a non-invasive manner with the help of aerosol generators such as inhalers, nebulisers etc. [ 2 , 3 ]. Once inhaled, the powdered/aerosolised drugs are transported along the respiratory tract where they deposit depending on their physio-chemical properties as well as breathing characteristics and physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pump without the valve also has the advantage of delivering high-viscosity medium, macromolecules and biologically active cells. Also, the structure was further downsized to produce a flow at the micrometer level, which can meet the requirement of the high-precision fields such as drug delivery and biomedical applications [57,80,81]. The advantages of the piezoelectric pump with active, check valve and valveless pump when compared with the other pump mentioned above are shown in figure 2, also, the comparison of the pump with active, check valve and valveless pump are listed in figure 2.…”
Section: Comparison Of Different Valve and Working Principles Of Valv...mentioning
confidence: 99%
“…Atomization, a process commonly observed through various spray mechanisms in our daily lives, also holds crucial significance in industrial applications like inkjet printing. 1 Consequently, atomization techniques have become invaluable tools with applications spanning a wide spectrum.…”
Section: Introductionmentioning
confidence: 99%